Pyloric stenosis due to brunneroma masquerading as peptic ulcer complication - Kumar, Shailesh; Alam, Mohammad Sarwar; Akbal, Shazid; Choudhary, Tayod Kumar (Indian Journal of Case Reports, 2018)
A 42-year-male presented to the surgical emergency with features of severe gastric outlet obstruction. On investigation, upper gastrointestinal series showed features suggestive of a near complete gastric outlet obstruction. Endoscopy revealed multiple antral ulcers with near complete pyloric stenosis, features suggestive of complications arising out of antral ulcers. Biopsy report revealed Brunner’s gland hyperplasia. A unique aspect about the case is the finding of antral ulcers associated with Brunner’s gland hyperplasia. The patient underwent laparoscopic distal gastrectomy with gastrojejunostomy. A high index of suspicion of Brunner cell hyperplasia in case of the patient presenting with features suggestive of pyloric stenosis is the crux of diagnosis in view of the malignant potential of Brunner cell hyperplasia.